Impacts of Diuretic Use in Pre-Dialysis Chronic Kidney Disease Patient in a Tertiary Care Hospital - Ramesh, Midhun; Nair, Sujith S; V, Mridul K; Benny, Aleena; R V, Ameesha; C, Gopika (Indian Journal of Pharmacy Practice)
Background: CKD is a global health concern with an estimated prevalence of 13.4%. Blood pressure can be a cause or consequence of CKD. In patients with Chronic Kidney Disease (CKD), hypertension is a common illness that contributes to the progressive loss of renal function towards end stage renal disease as well as cardiovascular events including heart attacks and stroke. Salt and water retention are caused by decreased kidney function, which finally causes volume expansion and elevated blood pressure. Diuretics therapy has been a cornerstone of care for CKD patients, especially for fluid excess and hypertension. In addition to their beneficial effects, diuretic usage is linked to negative renal outcomes. Objectives: The main aim of the study was to evaluate the association between diuretic use in Chronic Kidney Disease (CKD) progression and onset of end stage renal disease. Materials and Methods: A prospective observational study was conducted for 6 months among 107 patients of either sex those who underwent treatment for the pre dialysis chronic kidney diseases were included in the study. All the data were collected, documented and analysed based on standard protocol. Data collected were entered into Microsoft Excel. Statistical analysis was done by using Microsoft Excel. Results and Discussion: Out of 107 populations diagnosed with kidney disease, the study contains 71% males and 28% females. In this study kidney disease were seen commonly among age group of 27 to 91 years, showing that males were predominant for the development of chronic kidney disease. Commonly prescribed diuretics are Torsemide (100%), Furosemide (8.4%), and Aldactone (10.3%), Metolazone (37.4%). Torsemide is the drug that is most frequently prescribed. There is high burden of CKD among patients with type 2 DM and Hypertension. Majority of the patient have fluid overload and pulmonary oedema. There is a statistically significant reduction in weight and BMI in those patients who are on diuretics. The use of diuretics has not associated with any worsening of the renal function. Rather there was an improvement in the eGFR in those patients who was started on diuretics and whose fluid overload status was brought down to euvolemic status. The most widely used medications are beta blockers such Bisoprolol, Metoprolol, Carvedilol, and Nebivolol. The use of diuretics, including thiazide and loop diuretics, is not related with deteriorating eGFR; nevertheless, beta blockers have shown an improvement in eGFR that is statistically significant, pointing to a renoprotective impact. Since most of our patients were on metoprolol, we believe that metoprolol has a renoprotective effect on CKD patient but metoprolol in isolation has failed to improve eGFR. The beta blockers class themselves when analyzed against eGFR shows statistically improvement effect. Conclusion: The diuretics has not worsened eGFR but rather improvement was noted in the eGFR of patients who were on diuretics. Therefore, this study suggests diuretics does not have any deteriorating effect on the renal function but may contribute to improvement of eGFR if used. In our study, commonly prescribed medications did not impair eGFR function or impair renal function. Beta blockers, however, exhibit a renoprotective effect. Other drugs have failed in statistical terms to prove the renoprotective effect. Since most of our patients were on metoprolol, we believe that metoprolol has a renoprotective effect on CKD patients. But metoprolol in isolation has failed to improve eGFR. The beta blocker class themselves when analyzed against eGFR shows statistically improvement effect.
Keywords: Beta blockers; Chronic kidney disease; Diuretics; eGFR; Renoprotective